Cybersecurity in Digital Diplomacy: A Comparative Analysis of the United States and Kingdom of Bahrain (The International Journal of Educational Sciences and Arts, 2025)
In an era of digital diplomacy, cybersecurity has become a critical component of international relations. As diplomatic engagements shift to digital platforms, the risks associated with cyber threats-ranging from espionage and misinformation to cyber warfare-have escalated. This study provides a comparative analysis of cybersecurity strategies in digital diplomacy between the United States and Kingdom of Bahrain, two nations with distinct geopolitical positions and technological capabilities. The research employs an empirical approach, integrating international case studies to assess how both countries address cybersecurity challenges in diplomatic interactions. The findings highlight key differences in policy frameworks, institutional capacities, and international collaborations, offering insights into the effectiveness of cyber diplomacy in securing national and global interests. The study also explores emerging trends and best practices, providing policy recommendations for strengthening cybersecurity in diplomatic affairs.
Keywords: Cybersecurity; Digital diplomacy; Cyber threats; U.S. Cyber strategy; Bahrain cyber policy; Cyber Norms; Cyber espionage